Identification of the first congenital ichthyosis case caused by a homozygous deletion in the ALOX12B gene due to chromosome 17 mixed uniparental disomy - Zhang, Lei; Hu, Yanqiu; Lu, Jingjing; Zhao, Peiwei; Zhang, Xiankai; Tan, Li; Li, Jun; Xiao, Cuiping; Zeng, Linkong; He, Xuelian (Frontiers in Genetics, 2022)
Uniparental disomy (UPD) is a rare genetic event caused by a genetics error during gametogenesis and fertilization leading to two copies of a chromosome or chromosomal region inherited from one parent. MixUPD is one type of UPD that contains both isodisomic and heterodisomic parts because of meiotic recombination. Here, we present the first case of a little boy with ichthyosis who contained a homozygous deletion of exon 9 and part of exon 10 in ALOX12B gene due to maternal mixUPD revealed by whole-exome sequencing(WES). We also performed a retrospective analysis of 198 patients with ichthyosis caused by ALOX12B mutations. This is the first case who has milder clinical symptoms with a homozygous deletion in the hotspot region of ALOX12B gene. In addition, our patient has microtia and congenital stenosis of the external auditory canals, which is very rare in patients with the gene mutations. Our study reports the first case of Autosomal recessive congenital ichthyosis (ARCI) due to mixUPD of chromosome 17 and expands the spectrum of clinical manifestations of ARCI caused by mutations in the ALOX12B gene.